OPTIMALISASI PENYELESAIAN KASUS KDRT MELALUI MEDIASI - Apsari, Made Setyawati (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Cases of domestic violence are crimes committed by husbands against members of their family. Domestic violence (KDRT) often befalls women as wives. There are several forms or types of domestic violence including physical, psychological, sexual and economic violence. All forms of violence that occur in the household are caused by several factors such as the economy, education, socio-culture and infidelity. The act of domestic violence in some circles of society is considered normal in the household. While the impact of domestic violence can result in disruption of women's reproductive health, mental disturbance of children, divorce and also legal sanctions for the perpetrators. Domestic violence cases can be resolved through mediation. Mediation is an alternative in solving domestic violence cases. The litigants choose mediation because they think mediation can maintain confidentiality, there are no winners and losers, can fulfill a sense of justice, the process is faster and more concerned with the future of the household, family and children's future. The path of mediation in solving domestic violence cases must always be pursued by the litigants as well as by law enforcement.